2022
DOI: 10.1002/uog.24855
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound features of highly vascularized uterine myomas (uterine smooth muscle tumors) and correlation with histopathology

Abstract: What are the novel findings of this work?In our series of uterine myomas with high vascularization on ultrasound, the histological diagnosis was benign in 93% of cases, which included leiomyoma variant in 45% and adenomyoma in 6%. A malignant lesion was diagnosed in 7% of cases, all of which occurred in patients over 40 years of age. What are the clinical implications of this work?Our findings are useful in the clinical management of patients with a highly vascularized myoma identified during ultrasound assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…The echogenicity of the lesion has been suggested as a useful ultrasound feature to identify uterine sarcoma 12 . However, our findings are in line with those of Russo et al 24 , demonstrating that many benign lesions also show non-uniform echogenicity. We detected acoustic shadows in over 60% of uterine sarcomas, which is more than reported previously 12 .…”
Section: Discussionsupporting
confidence: 93%
“…The echogenicity of the lesion has been suggested as a useful ultrasound feature to identify uterine sarcoma 12 . However, our findings are in line with those of Russo et al 24 , demonstrating that many benign lesions also show non-uniform echogenicity. We detected acoustic shadows in over 60% of uterine sarcomas, which is more than reported previously 12 .…”
Section: Discussionsupporting
confidence: 93%
“…According to further GO and KEGG analysis, the DEGs were mainly enriched in connective tissue development and collagen-containing extracellular matrix, as well as the Wnt signaling pathway and JAK-STAT signaling pathway. The GO enrichment results are in line with our common experiments since UFs are composed of smooth muscle cells and varying amounts of fibrous connective tissue ( 33 ). The wingless-type (Wnt) signaling is considered a growth and development-related factor of the UFs, the elevated expression of WNT11, WNT16, and WNT5b, etc., were widely reported ( 34 , 35 ).…”
Section: Discussionsupporting
confidence: 89%
“…However, Ludovisi et al found that about a quarter of the LMS in their study had minimal or absent vascularization [10]. In the analysis of highly vascularized mesenchymal masses reported by Russo et al, only 7% of highly vascularized myometrial tumors were malignant, and all of them were in women over 40 years old [29]. Similarly, our experience shows that vascularization is not a conclusive factor.…”
Section: Discussionmentioning
confidence: 38%